Involving older people in research: practical considerations when using the authenticity criteria in constructivist inquiry - Brown Wilson, Christine; Clissett, Philip (Wiley, 2011)
Aim The purpose of this paper is to identify practical suggestions that could enable other researchers to consider how quality may be evidenced using constructivist principles including the perspectives of older people and their caregivers.